Impact of the Covid 19 Pandemic on the Financial Performance of Consumer Goods Industry in 2019-2020 on the Indonesia Stock Exchange - Ediningsih, Sri Isworo; Satmoko, Agung (RSF Conference Series: Business, Management and Social Sciences, 2021)
Covid -19 pandemic that announced by the Indonesian government on March 2, 2020, may have an impact on the company’s financial performance, marked by layoffs, decreased productivity, and decreased purchasing power of the people. This study aims to determine the financial performance of companies in the consumer goods industry sector in 2019 - 2020 (food and beverage sub-sector with pharmaceutical sub-sector) listed on the Indonesia Stock Exchange. The financial performance referred to in this study is measured by Current Ratio/CR, Debt Ratio/DR, Total Asset Turnover/TATO, Return On Equity/ROE, and Price Earning/PE. This study found that the financial performance of companies in the consumer goods industry and the financial performance of companies in the food and beverage sub-sector as measured by CR, DR, TATO, and PE increased, but ROE decreased during the pandemic Covid-19. On the other hand, the financial performance of the pharmaceutical sub-sector companies as measured by DR, TATO, ROE, and PE increased, and CR decreased during the Covid-19 pandemic.